Plant used by birds in coffee landscapes of Nariño, Colombia - Castillo R., Yulieth Viviana; Calderón Leytón, Jhon Jairo (Revista de Ciencias Agrícolas, 2017)
Plants are an important food resource for birds in coffee landscapes therefore the coffee plantations heterogeneity of guarantee its availability. Understanding the interactions between birds and plants is important for the biodiversity conservation in coffee landscapes. In this investigation, we present an initial list of plant species used by birds in coffee landscapes, in rural areas of the municipalities of Colón-Génova, La Unión, Arboleda and San Pedro de Cartago (Nariño, Colombia). The results showed that frugivorous birds fed from at least 25 species, nectarivorous birds from eight species and insectivorous birds foraged from nine species. The results obtained allow us to propose a list of potential plants (native and introduced), used as a food and foraging resource by birds, which could be useful for coffee landscapes management through the implementation of propagation and production strategies for coffee landscapes restoration.